The Influence of Financial Literacy and Lifestyle on Financial Management of Students at the Faculty of Economics and Business, UTP Surakarta - Hanifa Shulha; M. Tri Aditya Nugroho; Fiki Hendro Y; Zandra Dwanita Widodo (Asian Journal of Applied Business and Management, 2023)
The aim of this research is to find out how FEB UTP Surakarta students manage their finances in relation to their lifestyle and level of financial literacy. The sample for this research consisted of 50 Management and Accounting study program student’s class 2020, 2021, 2022, and 2023. This data collection approach combines a voluntary respondent sampling strategy with non-probability techniques. Data was collected through an online questionnaire and multiple linear regression was used to evaluate the results. The SPSS V23 application is used to analyze primary data in the form of respondent responses. The results of the F Test conclude that the independent variables together can be called feasible. The Adjusted R Square value shows a result of 33.6%. so that financial literacy and lifestyle influence financial management by 23.6%, the rest is influenced by other variables.